MISUNDERSTANDING OF THE INDONESIAN HUMAN RIGHTS ACTIVISTS ON THE APPLICATION OF THE DEATH PENALTY - Tajul Arifin (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2016)
AbstractThis research mainly uses statistical data published by the United Nations Office on Drugs and Crime (UNDDC) in April 2014 to support the hypothesis of this research that “Human Rights Activists in Indonesia as in other countries have failed in comprehending the wisdom (hikmah) of the application of Capital Punishment”. This study found that: (1) the hypothesis of this research was strongly supported by the data; (2) the application of Syari`ah Criminal Law in Saudi Arabia has been an unchallenged proof for the wisdom (hikmah) behind the application of Capital Punishment by keeping the level of murder crime to a low rate which sharply contrast to many countries which apply positive laws which are based on a social contract between the ruler and the ruled, such as in The United States and Mexico; and (3) In upholding the true justice in Islamic Criminal Law, punishment can only be awarded to the criminals in a society where the Islamic ideal of social justice has been achieved. AbstrakPenelitian ini menggunakan data statistik yang diterbitkan oleh United Nations Office on Drugs and Crime (UNDDC) pada bulan April 2014 untuk mendukung hipotesis dari penelitian ini bahwa